Keberadaan Mahkamah Konstitusi Dalam Sistem Ketatanegaraan Republik Indonesia: Kekuasaan, Kewenangan, Sistem Ketatanegaraan, Konstitusi - Shafira Muqsitha; Arif Wibowo (Jurnal Penelitian Multidisiplin, 2023)
One of the most important agendas of demands for reform and democracy is the establishment of an Indonesian constitutional system based on the notion of people's sovereignty and a rule of law (rechstaat). Therefore, in the context of strengthening the legal system which is expected to be able to bring the Indonesian people to achieve their aspired statehood goals, the amendment to the 1945 Constitution is a strategic step that must be carried out carefully by the Indonesian nation. Talking about the legal system is of course inseparable from the issue of legal politics, because it is legal politics that determines the legal system as desired. Changes in the constitutional system that occurred resulted in changes in the political, cultural and legal systems in Indonesia. Therefore, the younger generation must become agents of change in the life of the state constitutionally by taking part in the dynamics of the constitutionality of the nation and state. To foster a culture of constitutional awareness, it is necessary to understand the basic values and norms which are the material content of the constitution. Thus, the idea of establishing a Constitutional Court is an effort aimed at the correct administration of power and state administration in accordance with the basic law or constitution. The Constitutional Court is one of the state institutions that has the authority to exercise independent judicial power to administer justice, is responsible for managing its own organization, personnel, administration, finances, and can further regulate matters necessary for the smooth implementation of its duties and authorities.